Changes in the chemical properties of peat soil during establishment of pineapple / Salwa Adam and Noor Azimah Darus - Adam, Salwa; Darus, Noor Azimah (2012)
Burning practice in replanting of pineapple in this country is common. The crop residues of pineapple are recycled through burning before planting. Burning had an impact on physical and properties of peat soil. This study was aimed to determine the effect of burning on the chemical properties of peat soils and to determine the volume (m3) of peat lost due to burning during site preparation. Peat soils were sampled before, and after burning, and after one crop cycle and were analysed for pH, K, Ca, S. Mg, Fe and Zn. The nutrient elements were determined using inductively coupled plasma- optical emission spectroscopy (ICP-OES). The result indicated that pH pH, K, Ca, S, Mg, Fe and Zn were increased after burning. The nutrient flush from burning however could have contributed towards improving the low pH of peat soil which eventually increased the plant available nutrient. The increasing of soil pH is probably due to the increased of Ca and Mg after burning. However nutrient flush from burning was short lived. The flush lasted for about one year or less in the soil. The reduced nutrient was attributed to leaching and plant uptake. Residues burning also caused partial burning of the peat material itself, thereby will reduce peat volume and thickness due to combustion of peat material to produce carbon dioxides (COz). Burning practices resulted in a positive immediate impact in the terms of nutrient flush and improved pH, but could be resulted in substantial loss of peat in the long run. Other possible alternative to burning of plant residues included chipping and subsequently allowed them to decompose naturally.